2021
DOI: 10.1108/prr-12-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Asian community participation in biosphere reserves

Abstract: Purpose Managing biosphere reserves (BR) have become more challenging regarding the socio-cultural conflict between communities and BR administrators. For the past two decades, community participation (CP) has become the central narrative for BR management practices in Asia. This paper aims to set out to analyse the current literature because of the paucity of systematic reviews on CP in Asian BR. Also, it proffers possible solutions to enhance biosphere performance. Design/methodology/approach In total, 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…A total of 21 years period is a satisfactory time to evaluate the progress of previously published articles concerning GB and implementation in Africa. This agrees with Jaafar et al (2021) that used 19 years duration as satisfactory for a review paper. The selection approach adopted for articles was based on peer-reviewed published papers.…”
Section: Eligibility and Exclusion Criteriasupporting
confidence: 90%
See 1 more Smart Citation
“…A total of 21 years period is a satisfactory time to evaluate the progress of previously published articles concerning GB and implementation in Africa. This agrees with Jaafar et al (2021) that used 19 years duration as satisfactory for a review paper. The selection approach adopted for articles was based on peer-reviewed published papers.…”
Section: Eligibility and Exclusion Criteriasupporting
confidence: 90%
“…Scopus and Web of Science were the main databases employed and supported with selected published articles from Google Scholars. Jaafar et al , 2021 reported that journals in the Web of Science database are over 33,000 and 256 disciplines coverage. Whilst Scopus database is over 22,800 articles and 5,000 publishers.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of these databases was due to their reliability and comprehensive coverage of academic journals. According to Jaafar et al (2021), the number of Scopus database journals exceeded 22,800 journals and 5,000 publishers, while the Web of Science database covers over 33,000 journals and around 256 disciplines, which explains why Web of Science and Scopus are considered the most reliable academic databases.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the studies mentioned above have highlighted some critical roles multi-stakeholders play in achieving ecotourism sustainability. Researchers such as Salman et al (2021c) andJaafar et al (2021) have noted that multiple stakeholders are key to implementing ecotourism; therefore, their roles should be adequately understood. This calls for leadership among multi-stakeholders.…”
Section: Role Of Multi-stakeholders In Achieving Sustainable Ecotourismmentioning
confidence: 99%